P5-S7.07 Chlamydia screening in Cornwall: How often do young people get retested?. (10th July 2011) - Turner, K; Trela-Larsen, L; Gates, P; May, M; Horner, P
Abstract : Aim: To analyse the uptake of screening and rescreening in Cornwall, UK within the National Chlamydia Screening Programme (NCSP). Methods: We tested for any association between gender, age, test result and the probability of retesting. The time between tests was estimated using a Cox proportional hazards model and we tested whether the result of first test or gender influenced whether or not individuals were retested. Results: Between 2003–2009, 66 513 tests in 46 950 individuals were analysed. Most people were tested once. During this period the number of tests increased dramatically and the positivity declined (shown in Abstract P5-S7.07 table 1 ). Compared with those negative at the first test, positive cases were more likely to be retested and were retested sooner. Abstract P5-S7.07 table 1 Positivity among those tested in Cornwall 2003–2009. Discussion: We found that even in an area which has achieved high screening coverage, few people were re-screened. However, positive cases are more likely to be retested than negatives. This detailed county level analysis will provide information to policy makers to develop a long-term, sustainable and effective screening strategy.